Enriching behavior patterns with learning styles using peripheral devices - Duraes, Dalila (2019)
The human being is currently under an increased demand for attention, a result of a society that is moving faster. In most of the so-called developed countries, workers have nowadays increasingly busier activities. This makes them stretch their limits to find time for children, sports activities and other. This necessary extra time is frequently obtained at the expense of shorter periods of sleep or rest and with a cost in terms of pressure and stress. In this paper, we present a non-intrusive distributed system for enriching behavior patterns applying learning styles in a class of students which was considered as a team. It is especially suited for teams working at the computer. The presented system is able to provide real-time information about each individual as well as information about the team. It can be very useful for teachers or managers to identify potentially distracting events or individuals, and to detect the onset of mental fatigue or boredom, which significantly influence attention. In summary, this tool can be very useful for the implementation of better human resource management strategies, namely in the classification of learning style and the monitoring of the level of attention of each user.